2021
DOI: 10.1103/physreva.104.l060602
|View full text |Cite
|
Sign up to set email alerts
|

Ability of unbounded pairs of observers to achieve quantum advantage in random access codes with a single pair of qubits

Abstract: Complications in preparing and preserving quantum correlations stimulate recycling of a single quantum resource in information processing and communication tasks multiple times. Here, we consider a scenario involving multiple independent pairs of observers acting with unbiased inputs on a single pair of spatially separated qubits sequentially. In this scenario, we address whether more than one pair of observers can demonstrate quantum advantage in some specific 2 → 1 and 3 → 1 random access codes. Interestingl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 72 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…It can be observed that each of the above three states is entangled for the whole range of λ except at λ = 0. This result demonstrates the following interesting aspect of the generalized entanglement swapping protocol with the POVM (24). This protocol creates entanglement in the pair (1,4).…”
Section: Entanglementmentioning
confidence: 61%
See 4 more Smart Citations
“…It can be observed that each of the above three states is entangled for the whole range of λ except at λ = 0. This result demonstrates the following interesting aspect of the generalized entanglement swapping protocol with the POVM (24). This protocol creates entanglement in the pair (1,4).…”
Section: Entanglementmentioning
confidence: 61%
“…Therefore, the above results indicate that the resulting state ρ 14|i (for all possible outcomes i) after completion of our generalized entanglement swapping protocol contingent upon using the POVM (24) with x = 0.3 is entangled, but does not violate the three-setting steering inequality [51] or the Bell-CHSH inequality. This is summarized in Table II.…”
Section: Bell Nonlocalitymentioning
confidence: 69%
See 3 more Smart Citations